The Impact of Organizational Commitment on the Job Satisfaction of College Teachers in the College of Business Administration of Negros Oriental State University - Jaysone Christopher M. Bancoro (East Asian Journal of Multidisciplinary Research, 2023)
Teachers are at the core of society’s education and literacy, making them an indispensable workforce. While the profession offers a noble cause, it is not without challenges and difficulties. The institution where they belong is expected to provide them with the necessary support so they can perform their job well. This study looks into the relationship between the organizational commitment levels and job satisfaction of 29 regular-fulltime faculty of the College of Business Administration of the Negros Oriental State University main campus. A survey questionnaire was administered to measure their affective, continuance, and normative organizational commitment levels, and job satisfaction. Through Pearson’s r, it was found that there is no statistically significant relationship between affective and continuance commitment to job satisfaction. Although not strong, there is a recorded significant relationship between normative commitment and job satisfaction. The results showed that organizational commitment is not a strong driver for job satisfaction and vice versa. Several factors may affect this result such as the demographic profile of the respondents and their innate interest in the profession. As the study has its limitations, further research can be conducted to explore other factors of job satisfaction and influences in the organizational commitment.